Asesmen Kontribusi Keuangan Syariah terhadap Pertumbuhan Ekonomi di Indonesia - Santoso, Moh. Herman Eko; Nurzaman, Mohamad Soleh (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2020)
Islamic finance is one of the most rapidly growing sectors in the financial system in Indonesia. At the same time the Indonesian economy also showed positive growth. The main objective of this research is to assess Islamic finance in Indonesia's economic growth. This paper analyzes empirically the relationship between the development of the Islamic financial system and economic growth in Indonesia. The data used are time series from 2012 to 2019. These data include disbursed Islamic bank financing, the amount of sovereign sukuk issuance and corporate sukuk as independent variables related to proxies for the development of Islamic financial systems and proxies for economic growth as dependent variable. For the analysis, the unit root test, cointegration test and granger causality test were done. The basic analysis used in this research is the Vector Error Correction Model (VECM), and the Granger Causality Test is used to determine the direction of causality. This study also uses the Impulse Response Function and Variance Decomposition to determine the shock of each variable against the other variables. Empirical results show there is a positive relationship between the growth of the Islamic financial sector and economic growth in Indonesia. This is evidence that the Islamic banking system and sukuk can encourage economic growth. Structural analysis on VECM through the analysis of Variance Decomposition obtained from the results of Islamic banks and state sukuk is the dominant variable that contributes to the shock of economic growth. Therefore, in terms of improving the Indonesian economy growth, disbursed Islamic bank financing and sukuk can be considered as an effective financial instrument.Keywords: Islamic Finance, Economic Growth, Vector Error Correction Model (VECM)Keuangan syariah adalah salah satu sektor dalam sistem keuangan di Indonesia yang tumbuh paling cepat. Pada saat yang bersamaan ekonomi Indonesia juga menunjukkan pertumbuhan yang positif. Tujuan utama dari penelitian ini adalah untuk menilai kontribusi keuangan Islam dalam pertumbuhan ekonomi Indonesia. Data yang digunakan adalah time series tahun 2012 hingga 2019. Data tersebut diantaranya pembiayaan bank syariah yang disalurkan, nilai penerbitan sukuk negara dan sukuk korporasi sebagai variabel independen yang mewakili proksi untuk pengembangan sistem keuangan syariah dan proksi pertumbuhan ekonomi sebagai variabel dependen. Untuk analisis, dilakukan uji unit root, uji kointegrasi dan uji kausalitas Granger. Analisis dasar yang digunakan dalam penelitian ini adalah model Vector Error Correction Model (VECM), dan Uji Kausalitas Granger digunakan untuk menentukan arah kausalitas. Penelitian ini juga menggunakan Impulse Response Function dan Variance Decomposition untuk menentukan dampak shock pada masing-masing variabel terhadap variabel yang lain. Hasil empiris menunjukkan bahwa terdapat hubungan positif antara pertumbuhan sektor keuangan syariah dan pertumbuhan ekonomi di Indonesia. Hal ini menjadi bukti bahwa sistem perbankan syariah dan sukuk dapat mendorong pertumbuhan ekonomi. Analisis struktural pada VECM melalui analisis Variance Decomposition diperoleh hasil bahwa pembiayaan bank syariah dan sukuk negara adalah variabel dominan yang berkontribusi terhadap shock pertumbuhan ekonomi. Oleh karena itu, dalam hal meningkatkan pertumbuhan ekonomi Indonesia, pembiayaan yang disalurkan bank syariah dan sukuk dapat dianggap sebagai instrumen keuangan yang efektif.Kata Kunci: Keuangan Syariah, Pertumbuhan Ekonomi, Vector Error Correction Model (VECM)